(untitled) (Bangladesh Journal of Medical Science, 2025)
Background and rationale: Stroke radically changes the life not only of the patient but also of their relatives. Family members experience this event no less, and sometimes even more, than the patient themselves. Suddenly, they bear a huge additional burden: in the first weeks, they balance between household chores, work, and frequent hospital visits. After discharge, a complex process of caring for a bedridden patient begins. If the recovery of lost functions is prolonged, and aspects such as mobility, memory, speech, and self-care skills do not return, relatives accumulate chronic fatigue— both emotional and physical—as well as what is known as “caregiver fatigue.” Like the patient themselves, the family member providing care experiences an overwhelming sense of anxiety, and sometimes they too lose hope of returning to the previous life, which now seems distant and carefree. Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 663-673